Intracellular biogenic silver nanoparticles for the generation of carbon supported antiviral and sustained bactericidal agents - Vijayakumar, P. S.; Bhagavatula L. V. Prasad (Langmuir, 2009)
Intracellular silver nanoparticles produced by exposing silver ions to the fungus Aspergillus ochraceus were heat-treated in nitrogen environment to yield silver nanoparticles embedded in carbonaceous supports. This carbonaceous matrix embedded silver nanoparticles showed antimicrobial properties against both bacteria (Gram-positive and Gram-negative) and virus (M 13 phage virus). The bactericidal effects were noticed even after washing and repealed exposure of these carbon supported silver nanoparticles to fresh bacterial Cultures, revealing their sustained activity.